THE PROBLEMS IN IMAM-HATIP HIGH SCHOOLS ACCORDING TO SCHOOL MANAGERS - Baltacı, Ali (ILAHIYAT BILIMLERI ARASTIRMA VAKFI, 2019)
Imam-hatip high schools, which are opened for educating the qualified religious officials required by the society, are the institutions where religious education, which is a privileged area within the general education system, is offered at the level of secondary education. As in all schools in the general education system, different types of problems are encountered in imam-hatip high schools that have a religion based education concept. The task of the school managers is to find permanent and acceptable solutions to the problems in school. School managers who apply a wide variety of methods for this purpose can bring unique solutions to problems. The problems faced by the managers of Imam Hatip High School covered by the major responsibilities of any school manager. Imam-hatip high school managers are mostly responsible for (1) religious education curricula, (2) students, (3) teachers and other staff, (4) financial resources, and (5) other services provided by the school. While this broad area of responsibility seems to be somewhat unfavorable, the desire to hold power inherent in the management task, or to serve religious education as part of the case, is more dominant in school managers to choose school management than to teach.
Keywords: Psychology of Religion; Religious education; imam-hatip high school; school managers problem sources; solution strategies